PENGARUH PENGGUNAAN MINYAK KELAPA DALAM RANSUM TERHADAP BOBOT BADAN AKHIR, BOBOT DAN PERSENTASE KARKAS, SERTA PERSENTASE LEMAK ABDOMINAL PADA AYAM BURAS SUPER - Nelwan, Yosua; Leke, Jein R.; Sompie, Florencia N.; Laihad, Jacqueline T. (ZOOTEC, 2019)
UTILIZATION EFFECT OF COCONUT OIL IN RATION ON BODY WEIGHT, PERCENTAGES OF CARCASS AND ABDOMINAL FAT IN SUPER NATIVE HENS. This study was conducted to evaluate utilization effect of coconut oil in ration on body weight, percentages of carcass and abdominal fat in super native hens. This study was involving hundred unsexed super native hens at ages of eight weeks with the average initial body weight of 862.24 g ± 44.13 g. The treatments were ration without coconut oil (CO) utilization (R0), ration of 99.5% basal added with 0.5% CO (R1), ration of 99% basal added with 1% CO (R2), ration of 98.5% basal added with 1.5% CO (R3), and ration of 98.0% basal added with 2.0% CO (R4). The completely randomized design was applied as design with five treatments consisted of five replications at each treatment. Each experimental unit was put four heads of super native hens. The significant treatments were tested by Duncan’s test. Variables measured were life body weight, slaughter body weight, carcass weight and carcass percentage as well as abdominal percentage. Results showed that utilization effect of coconut oil in ration had the same effects on percentages carcassand abdominal fat, but had significant effect on life body weight and carcass weight. Therefore, it was concluded that utilizatilization of coconut oil up to 2 percents in ratio increased life body weight and carcass weight. Keyword: carcass weight, coconut oil, super native chicken.